Objective and subjective vasomotor symptom outcomes in the CBT-Meno randomized controlled trial. (2nd September 2020) - Green, S. M.; Donegan, E.; McCabe, R. E.; Fedorkow, D. M.; Streiner, D. L.; Frey, B. N.
Abstract: Objective: Vasomotor symptoms (hot flashes, night sweats) are common during the menopausal transition. Pharmacotherapy is effective but is associated with health risks for some women. There is an increasing demand for non-pharmacological interventions. The CBT-Meno protocol is a psychological intervention targeting a range of common menopausal symptoms. We compared the impact of CBT-Meno vs. waitlist on objective and subjective measures of vasomotor symptoms and on the relationship between vasomotor symptoms and sleep difficulties. Materials: The participants were 36 perimenopausal or postmenopausal women with co-occurring depressive symptoms who participated in the CBT-Meno trial (clinicaltrials.gov NCT02480192). Subjective measures included the Hot Flash Related Daily Interference Scale, the Greene Climacteric Scale, and the Pittsburgh Sleep Quality Inventory. Objective (physiological) and 'in-the-moment' measures of vasomotor symptoms were assessed with sternal skin conductance. Results: Greater improvements in vasomotor 'bothersomeness' and 'interference' were observed in the CBT-Meno condition compared to the waitlist condition. No between-group differences were observed in vasomotor frequency (subjectively or objectively recorded) or severity ratings. Sleep disturbance was unrelated to objectively measured vasomotor symptom frequency. Conclusion: The CBT-Meno trial improved subjective but not objective (physiological) measures of vasomotor symptoms. Self-reported sleep difficulties were unrelated to subjective or objective vasomotor symptoms.